2017
DOI: 10.1016/j.cedpsych.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Implicit intelligence beliefs of computer science students: Exploring change across the semester

Abstract: This study investigated introductory computer science (CS1) students' implicit beliefs of intelligence. Referencing Dweck and Leggett's (1988) framework for implicit beliefs of intelligence, we examined how (1) students' implicit beliefs changed over the course of a semester, (2) these changes differed as a function of course enrollment and students' motivated self-regulated engagement profile, and (3) implicit beliefs predicted student learning based on standardized course grades and performance on a computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 52 publications
2
19
0
1
Order By: Relevance
“…Although in the current work students report relatively strong growth mindset to start, this may not be the case at STEM-focused universities and we do see their growth mindsets decline from pretest to posttest. This is similar to recent work on implicit theories of intelligence that found theories become more entity-oriented across the semester in a sample of introductory computer science students (Flanigan, Peteranetz, Shell, & Soh, 2017). In summary, future work seeking to increase the interest and continuation of students in STEM might benefit from transforming not only individual students’ mindsets but also shifting learning environments to growth-oriented ones.…”
Section: Discussionsupporting
confidence: 87%
“…Although in the current work students report relatively strong growth mindset to start, this may not be the case at STEM-focused universities and we do see their growth mindsets decline from pretest to posttest. This is similar to recent work on implicit theories of intelligence that found theories become more entity-oriented across the semester in a sample of introductory computer science students (Flanigan, Peteranetz, Shell, & Soh, 2017). In summary, future work seeking to increase the interest and continuation of students in STEM might benefit from transforming not only individual students’ mindsets but also shifting learning environments to growth-oriented ones.…”
Section: Discussionsupporting
confidence: 87%
“…While the importance of educators understanding student's implicit theories about intelligence concerning entity and incremental beliefs is acknowledged (Flanigan et al 2017), it is also of paramount importance for educators to understand what students perceive to be intelligent behaviour. A misalignment between student and teacher expectations has the potential to elicit many negative educational implications and therefore the knowledge of student beliefs can support the development of mutual understandings.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically within Science, Technology, Engineering and Mathematics (STEM) disciplines, Dai and Cromley (2014) elucidate the importance of students' developing and maintaining incremental beliefs towards their abilities. Critically, the adaptive nature of these implicit beliefs has been illuminated (Flanigan et al 2017;Shively and Ryan 2013) identifying the capacity for pragmatic attempts to positively affect educational change.…”
Section: Implicit Theories Of Intelligence As Predictors Of Academic mentioning
confidence: 99%
“…Some studies using the mindset scale with college students have reported some validity evidence, such as indicators of the measure's internal structure (e.g., Cronbach's alpha, omega-total, and factor analyses) and test-retest reliability (Burkley et al, 2010(Burkley et al, , 2017Dai and Cromley, 2014;Scott and Ghinea, 2014;Smiley et al, 2016;Flanigan et al, 2017). An important component of validity that has yet to be assessed with the mindset scale is response process validity, which means that respondents engage in a common set of cognitive processes when responding to the items (American Educational Research Association, American Psychological Association, & National Council on Measurement in Education, 2014; Bandalos, 2018).…”
Section: Introductionmentioning
confidence: 99%